Genetic Polymorphism of Matrix Metalloproteinase 9 and Susceptibility to Chronic Obstructive Pulmonary Disease: A Meta-analysis: Genetic Polymorphism of Matrix Metalloproteinase 9 and Susceptibility to COPD - Yang, Xiaoping; Yu, Yuanyuan; Wang, Yong; Jiang, Wen; Jiang, Wenqing; Yin, Bin (Journal of Medical Biochemistry, 2022)
Background: To systematically analyze the influence of genetic polymorphisms of matrix metalloproteinase 9 (MMP9) on susceptibility to chronic obstructive pulmonary disease (COPD). Methods: Relevant literatures reporting MMP9 and susceptibility to COPD in PubMed, Web of School, VIP, Wanfang and CNKI databases were searched using the key words “matrix metalloproteinases 9/MMP9, COPD/chronic obstructive pulmonary disease”. Data of eligible literatures were extracted and analyzed for the OR and corresponding 95% CI. Results: A total of 13 independent studies reporting MMP9-1562C/T and COPD patients were enrolled and analyzed. None of the genetic models revealed the relationship between MMP9-1562C/T and susceptibility to COPD. Subgroup analyses identified lower risk of COPD in Chinese population carrying the TT genotype for the MMP-9 rs3918242 relative to those carrying CT and CC genotypes (P=0.03, OR=0.67, 95% CI=0.46-0.97). Conclusions: Chinese population carrying the TT genotype for the MMP-9 rs3918242 present lower susceptibility to COPD relative to those carrying CT and CC genotypes.